Role of Angiogenesis Inhibitors in Colorectal Cancer: Sensitive and Insensitive Tumors - Bagnasco, L.; Piras, D.; Parodi, S.; Bauer, I.; Zoppoli, G.; Patrone, F.; Ballestrero, A. (Current Cancer Drug Targets, 2012)
Angiogenesis is a key factor in the carcinogenesis process. In oncological practice, angiogenesis inhibition, mainly through the blockade of the VEGF family and its receptors, has been robustly demonstrated to produce clinical benefits and, in specific disease subsets such as colorectal cancer, to extend the overall survival of treated patients. VEGF is a multifunctional growth factor that mediates its functions through cognate receptors on endothelial cells and it has been discovered for its capability to induce macromolecule hyperpermeability in veins and venules. Several approaches have been taken to target angiogenesis in cancer: drugs that target one or more soluble ligands of the VEGF family, drugs that selectively inhibit one or more receptors of the VEGF receptor family, and drugs that inhibit VEGF receptor(s) among other, non VEGF-related targets. At present, two compounds have shown significant clinical activity, bevacizumab, Avastin® and aflibercept, Zaltrap®, and only one of these (bevacizumab) has so far been registered for use in clinical practice. In the present review, we explore and summarize the main features of the angiogenetic process, concerning in particular a common and potentially lethal disease as colorectal cancer. We overview the molecular pathways that characterize angiogenesis, focusing on VEGF family, the current applications and limitations of its blockade in oncology, and the hypothetical future perspectives of anti-angiogenic therapy.
Keywords: FOLFOX